Inhibition of Triggering Receptor Expressed on Myeloid Cell-1 Alleviates Acute Gouty Inflammation. (6th December 2019) - He, Yonglong; Yang, Qibin; Wang, Xiuxiu; Jia, Aimin; Xie, Wenguang; Zhou, Jingguo
Abstract : Gout is a prevalent form of aseptic inflammation caused by the deposition of monosodium urate (MSU) crystals in joints or tissues. Triggering receptor expressed on myeloid cell-1 (TREM-1) is a superimmunoglobulin receptor expressed on innate immune cells including granulocytes, monocytes, and macrophages. TREM-1 serves as a link between innate immunity and adaptive immunity, playing a crucial role in regulating inflammation and immune response. The purpose of this study was to investigate the potential role of TREM-1 in THP-1 cells and peripheral blood mononuclear cells (PBMCs) from patients with gouty arthritis (GA). In the current study, we found that the mRNA and protein levels of TREM-1 increased in PBMCs from GA patients and soluble TREM-1 in plasma as well. In addition, an increased level of TREM-1 was observed in THP-1 treated with monosodium urate (MSU) in vitro, along with upregulation of proinflammatory cytokines. Moreover, upon specific inhibition of TREM-1, Toll-like receptor 4 (TLR-4), and myeloid differentiation factor 88 (MyD88), the levels of MyD88 and proinflammatory cytokines were decreased after MSU challenge in THP-1 cells. Interestingly, inhibition of TLR-4 could enhance the effect of TREM-1 inhibitor in MSU-induced inflammation. Taken together, our findings suggested that TREM-1 could accelerate MSU-induced acute inflammation. Inhibition of TREM-1 may provide a new strategy for alleviating acute gouty inflammation.